EFEKTIVITAS PENYULUHAN MENGGUNAKAN CERAMAH DAN MEDIA TEBAK GAMBAR TERHADAP PENGETAHUAN DAN SIKAP TENTANG KARIES GIGI DI SDN MEKARSARI 03 TAMBUN SELATAN KABUPATEN BEKASI (Poltekkes Kemenkes Bandung, 2023)
In Indonesia, dental and oral health problems are one of the problems that people often complain about, especially among children. Based on the Basic Health Research (RISKESDAS) in 2018, the prevalence of caries in Indonesia was 88.8%, while the prevalence of caries in Indonesia for the 10-14 year age group was 73.4%. There are many cases, one of which is at SDN Mekarsari 03. Besides that, education has never been given so that it is necessary to carry out dental and oral health counseling from an early age. The purpose of the study was to determine the effectiveness of counseling using lectures and guessing media images on knowledge and attitudes about dental caries at Mekarsari 03 State Elementary School Tambun Selatan Bekasi Regency, this research was 49 students of class V using the Non-Probability Sampling technique with the type of Purposive Example. This type of research is a quasi-experimental. The results of the Wilcoxon test the difference in increasing student knowledge before and before counseling with lecture media and picture guessing have p = 0.000 < 0.05 and the difference in increasing student attitudes before and before counseling with lecture and picture guessing methods has p = 0.001 < 0.05. These results indicate that there are significant differences in students' knowledge and attitudes about dental caries before and before counseling using the lecture and picture guessing methods.